Optimizing water use efficiency and fruit quality of watermelon under mulched drip irrigation in arid regions - Liu, Zhiyuan; Zhang, Hengjia; Yu, Shouchao; Wang, Zeyi; Zhou, Chenli; Li, Haiyan (Frontiers in Plant Science, 2025)
IntroductionThe Hexi Oasis is located in the arid region of northwest China and is a crucial area for agricultural development. The region has a dry climate with scarce rainfall and a severe shortage of water resources. It has long relied on the traditional flood irrigation method, which has led to low efficiency in the utilization of water and soil resources and has hindered the sustainable development of agriculture.MethodsThis research was conducted in the Hexi Oasis from 2020 to 2021 using "New Farmer 8" watermelon as the experimental material. A field experiment was carried out to systematically explore the comprehensive effects of different water deficit patterns during different growth stages on the photosynthetic characteristics, yield, quality and water use efficiency of watermelons. Five treatments were set up: T1 with mild water deficit at both the seedling and mature stages (60%–70% FC, FC being the field capacity), T2 with mild water deficit at the seedling stage and moderate water deficit at the mature stage (50%–60% FC), T3 with moderate water deficit at the seedling stage and mild water deficit at the mature stage, T4 with moderate water deficit at both the seedling and mature stages, and CK with full water supply throughout the growth period (70%–80% FC) as the control.ResultsThe responses of watermelon photosynthesis, yield, and quality to different water deficit patterns were compared and analyzed to provide a scientific basis for efficient watermelon cultivation in arid oasis areas. The results showed that water deficit significantly reduced the net photosynthetic rate (Pn), transpiration rate (Tr), and stomatal conductance (Gs) of leaves, and the reduction increased with the severity of water deficit, with the reduction in Pn being smaller than that of Tr and Gs. Compared with CK, all water deficit treatments increased the irrigation water use efficiency (IWUE), with the highest IWUE in the T2 treatment (0.78 t·ha-1·mm-1), which was significantly higher by 10.50% than that of CK. The yield of the T1 treatment was the highest and showed no significant difference from CK, followed by T2, with no significant difference between T1 and T2. Water deficit treatments significantly increased the contents of soluble solids (SS), soluble sugar (SU), vitamin C (Vc), and soluble protein (SP), with the largest increase observed in the T2 treatment. The entropy weight–fuzzy matter-element comprehensive evaluation showed that the T2 treatment had the highest comprehensive score, followed by the T1 treatment. In the arid oasis area of Hexi, the multi-stage irrigation pattern of mild water deficit at the seedling stage combined with moderate or mild water deficit at the mature stage (T2 or T1) could significantly improve water use efficiency and fruit quality while maintaining yield, which represents a feasible strategy for achieving water-saving and high-quality watermelon production.